Optimizing the algorithm for assessing the efficacy of treatment for amblyopia in astigmats through the investigation of the features of meridional acuity characteristics as vector quantities - Oksana Kachan; Volodymyr Kolomiets (Ukrainian Society of Ophthalmologists, 2023)
Background: Refractive asymmetry associated with astigmatism may cause a special form of amblyopia, meridional amblyopia (MA). MA manifests itself as alterations in selective mechanisms of visual stimulus processing during recognition of contours of a certain orientation. Current routine examination of amblyopes does not include meridional acuity assessment and thus does not allow determining whether MA is present or not, as well as performing a more detailed evaluation of the efficacy of treatment for amblyopia in astigmats. Purpose: To optimize the algorithm for assessing the efficacy of stand-alone and complex methods of treatment for amblyopia in astigmats through the determination of the features of changes in visual acuities in orthogonal retinal meridians as vector quantities. Material and Methods: Twenty-four hyperopic astigmats with amblyopia (48 eyes) aged 5 to 12 years were involved in the study. Patients were treated by accommodative facility training only and, in 3 months, by complex therapy (accommodative facility training plus the use of device-based methods). Treatment course duration was 10 days. The results were assessed by changes in best-corrected visual acuity (Sivtsev Chart) and meridional separable visual acuity (MSVA) determined with the software which generates Landolt ring optotypes. Results: The study sample was found to be heterogeneous regarding the features of asymmetries in MSVA. Separable visual acuity in the horizontal meridian was equal in magnitude to that in the vertical meridian in 16.65% of patients. Asymmetries in separable visual acuity that may be considered MA were found in dominant and non-dominant (fellow) eyes in 83.35% of astigmats with amblyopia. Two different clusters were determined in the group with asymmetries in MSVA. Separable visual acuity in the horizontal meridian was higher than that in the vertical meridian in 35.45% of eyes in cluster 1, and lower than that in the vertical meridian in 47.85% of eyes in cluster 2. After treatment, mean separable visual acuity value in the vertical meridian was practically similar to that in the horizontal meridian in both groups for the dominant and fellow eyes, which allowed concluding that both methods were equally effective in treating the disease. However, the number of eyes with the same MSVA in orthogonal meridians increased by 10.41% after MA treatment with accommodative facility training only versus 18.75% after complex treatment. Conclusion: Assessing the features of changes in visual acuities in orthogonal retinal meridians as vector quantities enables obtaining principally new information on the performance of sensory functions in patients with amblyopia and assessing more reliably the efficacy of stand-alone and complex pleoptic methods as methods of treatment for MA.